Bayesian Inference for Categorical Data with Misclassification Errors - KURODA, MASAHIRO; GENG, ZHI (Advances In Statistics, Combinatorics And Related Areas, 2002)
In epidemiological studies, observed data are often collected subject to misclassification errors. In this paper, we discuss the Bayesian estimation for contingency tables with misclassification errors. Employing the exact Bayesian computations to obtain posterior means as estimates, we are faced with computational difficulties. In order to find the posterior distribution, we apply the data augmentation(DA) algorithm to misclassified categorical data.